Pola Asuh Permisif dan Dampaknya Kepada Anak Usia Dini (Teori dan Problematika) - Farida Rohayani; Wahyuni Murniati; Tirta Sari; Annida Ramdhani Fitri (Islamic EduKids: Jurnal Pendidikan Anak Usia Dini, 2023)
Basically every parent has the hope of having a child who is good, useful in terms of religion and education. This is of course inseparable from the parenting style adopted by parents, because the initial formation of character and children's education comes from the family environment. However, the current reality is that many parents do not understand their rights and obligations as parents, one of which is not upgrading knowledge about proper parenting or child development, causing parents to lack understanding of how to apply good parenting styles for children. This study aims to obtain information about permissive parenting and its impact on early childhood. The type of research used is descriptive qualitative research with data collection techniques in the form of observation, interviews and documentation. The source of data in this study is parents who are the object of research. The results of the study show that parenting styles in each family are different, this is caused by several factors, namely: parental education, economy, culture and environment. The parenting style applied in this study is permissive parenting. The permissive parenting style applied by parents has a great impact on children, causing children to be difficult to advise and teach good things, selfish, have no manners and manners, have no respect for parents, often fight and yell at parents in daily interactions, being lazy and impatient. This is due to the parenting style applied by parents and the lack of giving a good example or example to children. The characteristics of parents practicing permissive parenting are: 1. There are no clear rules; 2. Not consistent in giving punishments; 3. Giving excessive gifts; 4. Lack of involvement; 5. Does not provide clear consequences; 6. Avoid conflict; 7. Do not limit access to dangerous things; 8. Become a friend rather than an authority. Keywords: Permissive Parenting, Early Childhood.